The Effect of Service Quality and Satisfaction on the Loyalty of Parents of Nava Dhammasekha Cinta Kasih Students - Sugiarto Sugiarto*; Partono Nyanasuryanadi; Suherman Suherman (Riwayat: Educational Journal of History and Humanities, 2023)
The sustainability and success of educational institutions are influenced by various factors including the quality of service. The research objective was to analyze the effect of service quality on the tangible, responsiveness, reliability, assurance, empathy and parents' satisfaction on the loyalty of students' parents to Nava Dhammasekha Cinta Kasih in Sorong City. The study used a quantitative approach with proportional sampling of 84 people. Data collection techniques with questionnaires and analyzed using multiple linear regression. The results showed that service quality had a positive and significant effect on the loyalty of students' parents by the value of t count 3.197 t table 1.99045, sig value 0.002 0.05. Satisfaction of parents of students has a positive and significant effect on the loyalty of parents of students by the value of t count 5.216 t table 1.99045, sig value 0.001 0.05. Simultaneously the quality of service and the satisfaction of parents of students affect the loyalty of parents of students with a value of f count 179.733 t table 3.11226, sig value 0.001 0.05. The higher the quality of service and the satisfaction of parents of students at the Nava Dhammasekha Cinta Kasih school, the greater the loyalty of parents of students with a coefficient of determination of 0.82.